Relación entre la eficiencia del gasto público y la ejecución de proyectos de inversión en saneamiento básico en Loreto periodo 2010 –2023 - Rodriguez Rojas, Jorge Luis (2025)
This research analyzes the relationship between public spending efficiency and the execution of investment projects in basic sanitation in the Loreto region of Peru during the period 2010–2023. Using a quantitative, correlational, and non-experimental design, the study employed official data sources and applied both descriptive and inferential statistical techniques, with emphasis on Spearman's correlation coefficient. The findings reveal a direct and statistically significant relationship between budget execution efficiency and the expansion of water and sewage services, as well as between the number of projects implemented and access to these services. The general hypothesis was confirmed with a moderate correlation (ρ = 0.5371, p < 0.05), while the specific hypotheses displayed varying degrees of association, notably a strong correlation between the modified institutional budget and access to potable water (ρ = 0.9359). Based on the results, it is concluded that efficient public management not only improves financial execution but also has a concrete impact on reducing social service gaps. The study highlights the need to coordinate planning, budgeting, and territorial investment strategies to ensure sustainable interventions that genuinely improve the quality of life for the population.